Mother’s Experience Provide Burn First Aid to Younger Children - Hanifah Nur Laily; Elsa Naviati (Media Keperawatan Indonesia, 2019)
The incident of burns in children aged 1-4 years is risk get disabled and death. This is caused the children still do not understand about the danger and handling it. The role of a mother is important to give first aid to reduce the severity. First aid for burns that are still often given use such as toothepaste, saliva, coffe, soy sauce and margarine. The purpose of this study to describe the experience of mothers provide first aid in burns of children aged 1-4 years. This study was use qualitative phenomenologycal method. The sampel of this study was a mother have children aged 1-4 years who had suffered burn injury in periode of less than 9 mounth determined by the purposive sampling method. Collecting data was conducted by a in-depth interviews to 7 respondens. After 7 inteviews, found six main themes were identified: (1) first aid, (2) burns, (3) burns reaction, (4) psychological impact, (5) mother's perception of burns, (6) actions to reduce injury. Classification of burns found are mild to moderate burns. First aid for burns done by mothers using aloe vera, water, cooking oil, toothpaste, and tender care (oriflamme). The mother’s reaction to knowing that her child had burns was panic, worry, shoock, and pain. First aid for child burns given by the mother using aloe vera, water, cooking oil, toothpaste, and tender care (oriflamme).